Trends in depressive symptoms among adolescents aged 15 to 17 in Peru from 2014 to 2023 - Carlin-Morante, Carmen Herminia (2026)
Objetive: To determine the trend of depressive symptoms in adolescents aged 15 to 17 in Peru from 2014 to 2023. Materials and methods: Observational, multiple cross-sectional study, from secondary source. Adolescents without data on one of the variables included in the Patient Health Questionnaire (PHQ-9) were excluded. Since the Demographic and Family Health Surveys (ENDES) use complex sample designs, adjustment variables were required in the analysis. Results: A difference in the proportions of depressive symptoms was found between 2014 and 2023 (p value ˂ 0.001). Between 2014 and 2020, there was no major change in moderate to severe depressive symptoms; however, for the 2021-2023 period, the trend was upward. Overall, moderate to severe depressive symptoms in female adolescents were twice the value reported in male adolescents; this gap widened in 2021 and 2022. There was a greater impact in the “capital, large city” area in the period 2021-2023. Conclusions: Between 2014 and 2020, the proportion of moderate to severe depressive symptoms did not change significantly; however, the trend was upward for the 2021-2023 period. The proportion of moderate to severe depressive symptoms in women was almost twice that found in men. The "capital, large city" area was more affected between 2021 and 2023.